2007
DOI: 10.1007/s10096-007-0399-9
|View full text |Cite
|
Sign up to set email alerts
|

Entamoeba moshkovskii infections in Sydney, Australia

Abstract: Entamoeba moshkovskii is considered to be a free-living ameba, which is morphologically similar, but biochemically and genetically different, to Entamoeba histolytica and Entamoeba dispar. However, recent studies have suggested that E. moshkovskii may be a "potential" pathogen, with infections giving rise to diarrhea and other intestinal disorders. Microscopy and polymerase chain reaction (PCR) targeting the 18S ribosomal (r) DNA was performed on fecal samples collected from patients presenting with diarrhea a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
48
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 14 publications
5
48
0
1
Order By: Relevance
“…Parija and Khaimar (2005) reported gastrointestinal symptoms in Indian patients infected by the association of E. dispar with E. moshkovskii. A similar pathogenic potential was reported by Fotedar et al (2008) and Pritt and Clark (2008).…”
Section: Symptomatologysupporting
confidence: 87%
See 1 more Smart Citation
“…Parija and Khaimar (2005) reported gastrointestinal symptoms in Indian patients infected by the association of E. dispar with E. moshkovskii. A similar pathogenic potential was reported by Fotedar et al (2008) and Pritt and Clark (2008).…”
Section: Symptomatologysupporting
confidence: 87%
“…The fact is that infection with E. moshkovski is not uncommon and has a higher prevalence than infection with E. histolytica. The same was found in India (Parija and Kairnar, 2005), in homosexual patients with gastrointestinal symptoms in Australia (Fotedar et al, 2008), in two healthy adults in Tunisia (Ben Ayed et al, 2008a), and in a cohort of HIV-suspected or confirmed patients in Tanzania (Beck et al, 2008). All these studies also highlighted the important prevalence of E. moshkovski mono infection.…”
Section: Global Distributionmentioning
confidence: 54%
“…But it is not clear E. moshkovskii caused the observed symptoms. Some other studies have proposed E. moshkovskii to be likely an entropathogen in patients presenting with gastrointestinal symptoms (Foteder et al, 2008;Nazemalhosseini-Mojarad et al, 2010a;Parija and Khairnar, 2005). out of 3,825 stool samples were collected from patients with gastrointestinal disorders in Iran, 2 E. moshkovskii (3.45%), and one mixed E. dispar/E.…”
Section: Discussionmentioning
confidence: 98%
“…The organism is mainly free-living amoeba that rarely infects humans (Clark and Diamond, 1991;Clark and Diamond, 1997). A high incidence of E. moshkovskii infections was reported in stool specimens from Bangladesh and Australia and Turkey (Ali et al, 2003;Foteder et al, 2008;Tanyuksel et al, 2007). Three E. moshkovskii infections and one simultaneous infection with E. moshkovskii and E. dispar have also been reported in Iran (Nazemalhosseini-Mojarad et al, 2010a;Solaymani-Mohammadi et al, 2006).…”
Section: Introductionsmentioning
confidence: 99%
“…E. moshkovskii, another morphologically indistinguishable human parasitic Entamoeba, has not been mentioned, nor has it been considered a contributor to prevalence fi gures in endemic areas 11 . Molecular techniques that can differentiate all studied species of Entamoeba, including E. moshkovskii, in human specimens have already been reported in Italy, Bangladesh, India, Australia, Turkey, Iran, and Malaysia [31][32][33][34][35][36] .…”
mentioning
confidence: 99%